MOTIVATIONAL STRATEGIES USED BY AN ENGLSH TEACHER AT HAND FORTUNA CENTER - Maria P Rohi; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2017)
This is a qualitative study on the use of motivational strategies by the English teacher at Hand Fortuna Center. This study was based on Dörnyei’s (2001) theory about motivational strategies and focused on the interaction between the teacher and his students in the classroom. The data were collected by using video recording and interview. The observation was done in three meetings within two weeks. The duration of the class was 90 minutes for each meeting. The findings showed that the teacher used five out of eight motivational strategies in the classroom. There were making learning stimulating and enjoyable, protecting the learners’ self-esteem and increase their self-confidence, presenting task in a motivating way, allowing learners to maintain a positive social image, and promoting cooperation among the learners. For the interview, the writer found that the reason why the teacher used the motivational strategies. It was because the strategies could increase students’ motivation in learning language.